THE IMPORTANCE OF THE CHAIN OF CUSTODY OF EXPERT EVIDENCE IN DIGITAL AND DIGITIZED PROCESSES IN THE CIVIL SPHERE - Moura de Abreu Motta, Andréia (Revista Gênero e Interdisciplinaridade, 2023)
The research will bring an approach to the importance and problem of the non-existence or breaking of the chain of custody of evidence in civil procedure law, especially in digital or digitized expert evidence. It will demonstrate the need to implement and program together with civil procedural procedures an educational culture to demonstrate the need for the existence of the chain of custody of the traces, from the moment that all documentation enters the court secretariat, when it goes to the hands of the auxiliaries of justice – expert and attorney – until its return to the procedural records, to finally reach the judicial appreciation. Such acts are necessary to guarantee the transparency, fairness and integrity of the evidence, granting the broader right of defense regulated by the Federal Constitution. It will present at first a general conceptual approach. For the development of the work, documentary research, articles in the area and other bibliographies within the theme were used. Making sure that there is an enormous weakness in security with digital evidence in the civil procedural context, making the existence of a chain of custody necessary. Finally, it is worth noting the importance of implementing the chain of custody, together with the organizational culture to adapt a new way of functioning for the preservation of digital expert evidence in the civil sphere.